Tailored biomimetic nanoreactor improves glioma chemodynamic treatment via triple glutathione depletion and prompt acidity elevation - Ya Wen; Qiansai Qiu; Feng Feng; Yujuan Zhu; Jianquan Zhang; Zesheng Sun; Tuodi Zhang; Wei Shi; Jinlong Shi (Materials Today Bio)
Chemodynamic therapy (CDT) is an emerging antitumor strategy utilizing iron-initiated Fenton reaction to destroy tumor cells by converting endogenous H2O2 into highly toxic hydroxyl radical (OH). However, the intratumoral overexpressed glutathione (GSH) and deficient acid greatly reduce CDT efficacy because of OH scavenging and decreased OH production efficiency. Even worse, the various physiological barriers, especially in glioma, further put the brakes on the targeted delivery of Fenton agents. Herein, by exploring the thiol reaction potential of 5,5′-dithiobis-2-nitrobenzoic acid (DTNB), we have constructed a tailored biomimetic nanoreactor to improve glioma CDT efficacy through synchronous GSH exhaustion and acidity elevation. The biomimetic nanoreactor was fabricated by employing DTNB to drive the nano-assembly of BSA molecules, followed by loading the carrier onto the cell surface of neutrophils via disulfide-thiol exchange. Upon sensing the inflammatory signal, the nanoreactor hijacked by neutrophils efficiently targets to the tumor site, which then dually depletes GSH by disulfide bond stabilizing the nanostructure and the following liberated Fe (III). In particular, the simultaneously released DTNB can not only consume the residual GSH, but also produce 5-thio-2-nitrobenzoic acid (TNB) promptly, resulting in accelerated Fenton reaction. Through in vitro and in vivo experiments, we demonstrate the exhaustive and synchronous regulation of Fenton chemistry could potentially serve as a novel CDT strategy for glioma.